2009
DOI: 10.1002/jqs.1268
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the East China Sea palaeoenvironment at 16 ka by comparison of fossil and modern Faviidae corals from the Ryukyus, southwestern Japan

Abstract: 2009. Reconstruction of the East China Sea palaeoenvironment at 16 ka by comparison of fossil and modern Faviidae corals from the Ryukyus, southwestern Japan.ABSTRACT: We conducted paired measurements of the Sr/Ca ratio and oxygen and carbon stable isotopes of a fossil Faviidae coral specimen (MYK90), age 16 ka, collected from near Miyako Island, the Ryukyus, southwestern Japan. Our study aimed to reconstruct the palaeoenvironment in the East China Sea at 16 ka by comparing the fossil sample with modern Faviid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Rheophytic plants are diversified throughout the world, although the distribution ranges of most species are confined to fairly small areas (van Steenis 1981(van Steenis , 1987; most rheophytes (75%) are endemic species distributed locally in narrow river areas (Kato 1999). Given the low dispersal abilities caused by highly confined habitats and present small distribution ranges, it seems difficult for the rheophytes of Ryukyu Ainsliaea to accomplish range expansion across islands during Quaternary glaciations, when a drier climate had developed in this region (Mishima et al 2009). Overall, the rheophytic species in the Ryukyu Ainsliaea may have evolved within the islands and persisted there to the present.…”
Section: Adaptive Diversification Of Rheophytes In the Ryukyu Ainsliaeamentioning
confidence: 98%
“…Rheophytic plants are diversified throughout the world, although the distribution ranges of most species are confined to fairly small areas (van Steenis 1981(van Steenis , 1987; most rheophytes (75%) are endemic species distributed locally in narrow river areas (Kato 1999). Given the low dispersal abilities caused by highly confined habitats and present small distribution ranges, it seems difficult for the rheophytes of Ryukyu Ainsliaea to accomplish range expansion across islands during Quaternary glaciations, when a drier climate had developed in this region (Mishima et al 2009). Overall, the rheophytic species in the Ryukyu Ainsliaea may have evolved within the islands and persisted there to the present.…”
Section: Adaptive Diversification Of Rheophytes In the Ryukyu Ainsliaeamentioning
confidence: 98%
“…3.26). ;Morimoto et al 2007 (diamand) ;and Su et al 2010 ( star) A record of Sr/Ca ratios and oxygen and carbon stable isotopes from a 16 ka fossil coral from the Ryukyus, southwestern Japan, showed that the annual mean SST was approximately 5 °C lower and SSS was locally higher at 16 ka than present conditions, suggesting weak East Asian summer monsoon activity and enhanced winter monsoons during the last glacial (Mishima et al 2009). …”
Section: The Holocenementioning
confidence: 94%
“…This reduced sensitivity may reflect the inclusion of diagenetically altered skeleton in geochemical analyses; no specific diagenetic screening was mentioned by the authors. Budd et al [2012]) forms massive colonies in the Indo-Pacific, with spaces between the ~10 mm diameter plocoid corallites increasing with greater water depth [Mishima et al, 2009;Seo et al, 2013;Veron, 2000b]. Colonies grow between 4.6 and 7.1 mm year −1 [Seo et al, 2013], with numerous septa and no well-developed paliform lobes [Veron, 2000b].…”
mentioning
confidence: 99%
“…O signatures recovered from the major growth axis of the corallite wall [Mishima et al, 2009]. However, reconstructions for SST based on the Sr/Ca paleothermometer were derived from a sensitivity of 0.060 mmol/mol/°C that was selected, not derived from modern coral records with a corresponding instrumental temperature record [Mishima et al, 2009].…”
mentioning
confidence: 99%
See 1 more Smart Citation